Identification of naturally occurring inhibitors in Xian-Ling-Gu-Bao capsule against the glucuronidation of estrogens - He, Liangliang; Xu, Chunxia; Wang, Ziying; Duan, Shuyi; Xu, Jinjin; Li, Chuan; Yao, Xinsheng; Gonzalez, Frank J.; Qin, Zifei; Yao, Zhihong (Frontiers in Pharmacology, 2022)
Xian-Ling-Gu-Bao capsule (XLGB), a well-known traditional Chinese medicine prescription, is widely used for the treatment of osteoporosis. It could significantly increase the levels of estrogen in ovariectomised rats and mice. However, this working mechanism has not been well elucidated. Considering that UDP-glucuronosyltransferases (UGT) enzymes are the important enzymes that inactivate and regulate estrogen activity in vivo, this study aimed to identify the bioactive compounds from XLGB against the glucuronidation of estrogens. First, thirty compounds were considered as the candidate bioactive compounds based on our previous studies including pharmacological evaluation, chemical profiles, and metabolic profiles. Second, the characteristics of estrogen glucuronidation by uridine diphosphate glucuronic acid (UDPGA)-supplemented human liver microsomes (HLM), human intestine microsomes (HIM), and expressed UGT enzymes were determined, and the incubation systems of their key UGT enzymes were optimized. Then, inhibitory effects and mechanisms of XLGB and its main compounds toward the key UGT isozymes were further investigated. As a result, estrogen underwent efficient glucuronidation by HLM and HIM. UGT1A10, 1A1, and 2B7 were mainly responsible for the glucuronidation of estrone, β-estradiol and estriol, respectively. For E1 and E2, UGT1A10 and 1A1 tended to mediate estrogen-3-O-glucuronidation, while UGT2B7 preferred catalyzing estrogen-16-O-glucuronidation. Furthermore, the incubation system for active UGT isoforms were optimized including Tris-HCl buffer, detergents, MgCl2 concentration, β-glucuronidase inhibitors, UDPGA concentration, protein concentration, and incubation time. Based on optimal incubation conditions, eleven, nine and nine compounds were identified as the potent inhibitors for UGT1A10, 1A1 and 2B7, respectively (IC50 < 4.97 μM and Ki < 3.35 μM). Among them, six compounds (bavachin, isobavachin, isobavachalcone, neobavaisoflavone, corylifol A and icariside II) simultaneously demonstrated potent inhibitory effects against these three active enzymes. Prenylated flavanols from Epimedium brevicornu Maxim., prenylated flavonoids from Psoralea corylifolia L. and salvianolic acids from Salvia miltiorrhiza Bge. were characterized as the most important effective compounds. The identification of potent natural inhibitors of XLGB against the glucuronidation of estrogen laid an important foundation for the pharmacodynamic material basis.